Students’ Knowledge and Production of English Lexical Collocations - Ardi Nugroho (Universitas Bunda Mulia, 2017)
Vocabulary teaching and learning is one of the important aspects of language that should be given proper emphasis since without vocabulary, communication would be very difficult, as we cannot express our ideas properly. Collocation, or the habitual co-occurrence of words, is one of the components of vocabulary. Research has shown that EFL learners often face difficulties when producing native-like collocations. This research is an attempt to explore the knowledge and production of English lexical collocations of EFL students, more specifically, students of the English Language and Culture Department at BundaMulia University. To collect the data, the writer distributed a lexical collocation test. The test is divided into four parts. The first two parts measure the students’ lexical collocation knowledge and the last two parts examine their production of lexical collocation. The test was distributed to BundaMulia University students in the English Language and Culture Department (BBI). The students are from the fourth and sixth semesters. The nature of this study is qualitative descriptive. The findings of this research reveal that the overall competence of the students in identifying and producing English lexical collocations is still quite low. The students still have difficulty identifying and producing collocations which are native-speaker-like. It is also found that their L1 influence the students in their identification and production of lexical collocations. Keywords: Knowledge, production, collocation